Halal Certification for Imported Meat in Johor: An Overview of Standard Operating Procedures and Compliance Challenges - Nur Damia Sahira Harsual Effendi; Setiyawan Gunardi (USIM Press, 2024)
The development of the Halal industry in Malaysia, particularly in providing Halal food, is increasingly recognized as an important sector, especially in the production of Halal meat products. Jabatan Kemajuan Islam Malaysia (JAKIM) and Jabatan Agama Islam Negeri (JAIN) have been established to ensure that products meet Halal standards and Syariah guidelines. As a Federal Government agency, JAKIM holds the authority to supervise matters related to Halal certification in Malaysia. However, despite the oversight of JAKIM and JAIN in managing Halal industry operations, this sector continues to face various challenges in ensuring that each product fully complies with Halal and Syariah standards. In 2021, a significant issue arose involving a meat company in Johor that illegally used a fake Halal logo and misrepresented Halal certification without proper approval from the Australian Halal certification body. This incident raised questions regarding the efficiency of the Standard Operating Procedures (SOPs) for Halal certification, especially concerning imported meat products. This article aims to describe the concept of Halal, explain the SOPs for Halal certification of imported meat, analyze the challenges in maintaining compliance with these SOPs, and propose solutions to enhance adherence. The methodology adopted for this research includes a qualitative approach involving library research and case study analysis, drawing on data and information from journals, books, and statutes related to Halal certification. The findings reveal that certain entrepreneurs still fail to comply with the Halal certification SOPs due to various challenges faced by authorities in enforcing compliance. Finally, the study highlights recommendations for improving the standards of Malaysian Halal certification to address these compliance issues.